A Geology of Media - Parikka, Jussi, 1976- (Book collections on Project MUSE., 2015)
Media history is millions, even billions, of years old. That is the premise of this pioneering and provocative book, which argues that to adequately understand contemporary media culture we must set out from material realities that precede media themselves-Earth's history, geological formations, minerals, and energy. And to do so, writes Jussi Parikka, is to confront the profound environmental and social implications of this ubiquitous, but hardly ephemeral, realm of modern-day life. Exploring the resource depletion and material resourcing required for us to use our devices to live networked lives, Parikka grounds his analysis in Siegfried Zielinski's widely discussed notion of deep time-but takes it back millennia. Not only are rare earth minerals and many other materials needed to make our digital media machines work, he observes, but used and obsolete media technologies return to the earth as residue of digital culture, contributing to growing layers of toxic waste for future archaeologists to ponder. He shows that these materials must be considered alongside the often dangerous and exploitative labor processes that refine them into the devices underlying our seemingly virtual or immaterial practices. A Geology of Media demonstrates that the environment does not just surround our media cultural world-it runs through it, enables it, and hosts it in an era of unprecedented climate change. While looking backward to Earth's distant past, it also looks forward to a more expansive media theory-and, implicitly, media activism-to come.